Well‐Posed Treatment of Space‐Charge Layers in the Electroneutral Limit of Electrodiffusion. Issue 12 (27th August 2015) - Stinchcombe, Adam R.; Mori, Yoichiro; Peskin, Charles S.
Abstract: The electroneutral model describes cellular electrical activity, accounting for ionic concentration dynamics without resolution of the fine spatial scales of the space‐charge layer. This is done by asserting that the ionic solution is electrically neutral at each point in space. However, electroneutrality is inconsistent with the original boundary conditions at cell membranes. We consider three separate methods of resolving this inconsistency that result in well‐posed models that are accurate approximations to a detailed model in which the space‐charge layer is fully resolved. A particular electrodiffusion problem is utilized to make the discussion specific.© 2015 Wiley Periodicals, Inc.